THE IMPACT OF ACCOUNTING INFORMATION SYSTEM ON ORGANISATIONAL PERFORMANCE IN CHINA - Yixuan , Wu; Arumugam , Dr. Dhamayanthi (Electronic Journal of Business and Management, 2021)
The business environment is evolving rapidly due to technological changes, advanced Information Systems (IS), and increased market competition. This study analyzes the critical role of the Accounting Information System (AIS)—a framework incorporating IT and IS to manage monetary and economic functions—on organizational performance in China. Using primary data from 200 respondents, the research employed various statistical tests, including descriptive analysis, normality and linearity tests, Pearson correlation, and multiple regression analysis. The study concludes that AIS significantly impacts the achievement of corporate success and overall organizational performance.